Sujeito-corpo-resistência: práticas discursivas em cenas escolares - Ribeiro, Eliziane Tainá Lunardi (2023)
This thesis, developed in the Doctoral Course of the Postgraduate Program in Education (PPGE), in the research line Special Education, inclusion and difference, and articulated to the research groups GEPE - Study and Research Group in Special Education and Inclusion and Rizoma - Policies, Curriculum and Education, aims to analyze how the educational practices of school scenes perform and invent subjects in constant movements of escape. That said, through teaching experiences and notebooks of everyday school life, a problematization is invented to move some clues and shuffle them: how do the educational practices of school scenes perform and invent subjects in constant movements of escape? To this end, School Scenes are constructed as materiality from School Minutes, inventing Episodes (practices of subject production) that give visibility to the extension of discourses on student-bodies, a body-other: [i]mobile, (in)disciplinary, (in)capturable and (in)correctable. Between the Episodes, movements of escape are mobilized, constituting the Thesis: educational practices and the school, crossed by other visibilities, produce subjects as bodies-resistance that cause escapes-blurring in the ways of being/doing another school. Therefore, the Thesis can be detailed through the invention of educational practices capable of, in another discourse about subject-bodies, giving visibility to bodies-resistance, which enable, with their performances, constant movements of escapes/blurrings. Bodies-resistance that beckon to other disputes in the relations of force, in order to review the educational practices themselves and the possibility of another school, sliding the production of subject to a body-other, in performance a body-power-resistance-knowledge.